Legal Protection for Teenagers in the Use of Social Media at SMKN 1 Bangkinang Kampar - Erdianto Effendi; Mukhlis Ridwan; Davit Rahmadan (Universitas Negeri Semarang, 2023)
The development of information and communication technology causes world relations to become borderless and causes significant social, economic and cultural changes that take place very quickly and give rise to new crimes. In the virtual world, people do various evil deeds (crimes) that cannot be done in the real world. The crime was committed by using electronic information facilities as a means of action. Social media can potentially be an alternative means of crime. No matter this is also done among teenagers. Through coaching and socialization on how to be wise and use social media among teenagers, it is hoped that there will be no more criminal cases stemming from the misuse of social media. The activity was carried out with the method of lectures, discussions and questions and answers for adolescent students of SMKN 1 Bangkinang.